The 2021 Portuguese Society of Ophthalmology Joint Guidelines with Paediatric Rheumatology on the Screening, Monitoring and Medical Treatment of Juvenile Idiopathic Arthritis-Associated Uveitis - Leal, I (2022)
Aim: To develop the first Ophthalmology joint guidelines with Paediatric Rheumatology with recommendations on the screening, monitoring and medical treatment of juvenile idiopathic arthritis-associated uveitis (JIA-U), endorsed by the Portuguese Society of Ophthalmology (SPO). Methods: A systematic literature review was conducted to include publications up to July 14th 2020, with no language restrictions, in order to include all the international position papers/guidelines concerning the medical management of JIA-U and randomised clinical trials assessing the efficacy and safety of medical treatment in this field. We searched through MEDLINE (PubMed), Scopus, Web of Science and Cochrane Library. The Delphi modified technique to generate consensus was used. Preliminary evidence statements were subject to an anonymous agreement assessment and discussion process using an online survey, followed by further discussion and update at a national meeting. A draft of the manuscript with all recommendations was then circulated among all participants and suggestions were incorporated. The final version was again circulated before publication. Results: Twenty-six recommendations were developed focusing on the following topics: general management (3), screening and follow-up of uveitis (4), treatment (17) and health education in JIA-U among patients and families (2). Conclusion: These guidelines were designed to support the shared medical management of patients with JIA-U and emphasize the need for a multidisciplinary approach between Ophthalmology and Paediatric Rheumatology regarding the comprehensive care of JIA-U. We acknowledge that updating these recommendations will be warranted in the future, as more evidence becomes available.